On 2-D polynomials and discrete-continuous systems - Trzaska, Zdzisław W. (Zielona Góra: Uniwersytet Zielonogórski)
Problems connected to the efficiency of the 2-D polynomials in solutions to practical problems are also considered. Examples illustrating possible applications of the presented approach are also demonstrated.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka